Islam & Mammon: The Economic Predicaments of Islamism By Timur Kuran (Princeton and Oxford: Princeton University Press, 2004. 194 pages.) (American Journal of Islam and Society, 2007)
In this brilliant contribution, Timur Kuran weaves six chapters into asound critique of the assumptions and practices of Islamic economics. In essence, he attacks the very foundation of Islamic economics, the prohibitionof interest, and then extends his critique to whether Islam’s traditionalredistributive instruments in achieving contemporary economic goalis feasible. The author’s intention is not simply to critique Islamic economics,but to bring the ideas espoused by the discipline into the realm ofmainstream social sciences and encourage serious scholarly consideration.The first two chapters summarize the basic tenets of Islamic economicswhile grounding the discipline in two central claims: that existing economicsystems have failed and that Islamic history proves the Islamic system’ssuperiority over others. Kuran dismisses the latter by revealing thatmodern economic problems had historical counterparts, that many conceptsand methods utilized by Islamic economists originated outside theIslamic world, and that applying ancient solutions to present problems isan inadequate approach.Islamic economics’ material expression has been confined to Islamicbanking, for which prohibiting interest is the sine qua non, and redistributionefforts. Profit and loss sharing techniques, namely, mudarabah andmusharakah, have been derived from classical Islamic jurisprudence inorder to avoid interest. These terms refer to practices whereby an individualentrusts an entrepreneur or an investor with an amount of capital that willyield a specified return. Kuran attacks these practices, asserting that theyremain mechanisms for charging interest on the grounds that since modernbanking is based on profit and loss sharing, these classical methods simplyallow bankers to avoid using the term interest ...